The Influence of Cash Sales Accounting Information Systems on Internal Control of Cash Sales: Study of One Company in The Consumer Goods Distributor Sector in Bandung - Ajeng Ayu Anggraeni; Maulana Yusup; Robbi Saepul Rahman; Jimmy Rusjiana (Majalah Bisnis & IPTEK, 2024)
This study seeks to determine and analyze the impact of variables. The research employed a quantitative methodology, explicitly utilizing a descriptive approach and verification methods such as correlation coefficient, simple linear regression, and coefficient of determination. The study included a population of 30 individuals, and the samples collected encompassed the entire community. According to the research findings on a consumer goods distributor company in Bandung, it can be concluded that the company's cash sales accounting information system (X) is performing well, with a score of 3.25. The internal control of cash sales (Y) is also reported to be entirely satisfactory, with a score of 3.19. The findings of this study indicate a significant correlation (correlation coefficient of 0.862) between the Cash Sales Accounting Information System and Cash Sales Internal Control. The Cash Sales Accounting Information System contributes to 74.3% of the variation in Cash Sales Internal Control (R square contribution). The remaining 25.7% is attributed to unexamined factors such as company policy.